Analysis of the Influence of Service Quality on Patient Satisfaction in Hospitals: Literature Review - Setyawan, Aris Kabib; Isnanto, Samto Hadi (Dinasti Publisher, 2025)
This study aims to analyze the effect of service quality on patient satisfaction in the context of health services. Previous studies have shown that service quality plays an important role in shaping patient satisfaction, which in turn affects the level of loyalty and perception of health facilities. Through a literature review approach, this study collects and analyzes various scientific articles, journals, and books that discuss factors that influence the quality of health services, such as dimensions of reliability, responsiveness, assurance, empathy, and physical evidence. The results of this review indicate that good service quality can increase patient satisfaction, which is reflected in reduced complaints, increased trust in medical personnel, and the tendency of patients to recommend health facilities to others. This study also identifies challenges and barriers in maintaining service quality, and suggests practical implications for hospital managers and health service providers in efforts to improve patient satisfaction. These findings are expected to provide useful insights for policy development in the health service sector.